On Etymological Interpretation of Northern Russian Words with the Meaning ‘to Lie, to Deceive’ (Dialect Words kolyzhit’, drevit’, obryazanit’, chmurit’ etc.) - V. S. Kuchko (Научный диалог, 2017)
The article is devoted to the search for the etymological interpretation of some words with the semantics of lies and deceit. Material for the study were the Russian dialectal lexemes functioning mainly in the Russian North (Vologda, Arkhangelsk and Novgorod dialects). In some cases the author refers to unpublished field records of a card file of the Dictionary of dialects of the Russian North, stored at the Department of Russian Language, General Linguistics and Speech Communication, Ural Federal University. Interpreted words were not previously considered in the etymological literature or have disputable interpretation that ensures the relevance and novelty of the research. Among the analyzed lexemes are dialect words kolyzhit’ ‘to lie’, drevit’ ‘to talk nonsense, to lie’, obryazanit’ ‘to deceive, to cheat’, chmurit’ ‘to pretend, to deceive’, gnezdit’ ‘to lie’, oturit’ ‘to cheat’, each of which is the subject of a separate part of the article. These words are considered as a part of the enclosing etymological-derivational nests. The analysis involves a typological semantic and derivational parallels, the author also refers to the motivational models of nomination, that contributes to the reliability of the results.